School-Based Management Policy and Its Practices at District Level in the Post New order Indonesia - Sumintono, Bambang (RMPI-BRIN, 2009)
The debacle of the collapse of the New Order regime in 1998 brought significant change to Indonesia’s public sector. Primary and secondary education since 1 January 2001 has been based on the new law about regional autonomy, and administered at district level rather than in the previously centralised and bureaucratic manner. At the school level, ideas about school autonomy emerged and became popular. In particular, the term ‘School Based Management’ (SBM) was seen as a panacea, and as a result, the central government issued a regulation to implement the practice of SBM. This article analyses the dynamics of the SBM policy as it was interpreted and implemented. The study was approached in two ways: through document analysis of the Ministry of National Education decree 044/U/2002 that promulgated SBM; and by soliciting and interpreting the perspectives and practices of stakeholders at district level through interviews, site studies and document analyses. The study found that the SBM policy as stated in the decree lacked clarity. The decree had been hastily introduced and emphasised structural changes at district and school levels without clarifying its underlying rationale or implementation guidelines.